Determining factors of academic success of first year BSc Dietetics students - Gresse, A.; Stansbury, C. (South African Journal of Higher Education, 2021)
It is broadly acknowledged that a host of factors influence the academic success of students, but there currently is a paucity of literature about this issue in the field of health sciences, and none in specifically Dietetics, in South Africa, and very little globally. This constitutes a significant knowledge gap in the field of higher education, as determining which factors are most important in facilitating the success of Dietetics students in a South African context, will make a significant contribution to understanding and assisting such students. The aim of this article is to report on a study that identified the key factors of success of first year BSc Dietetics students at one South African university. The aim of the study was to inform the design of interventions that would improve the performance and throughput of these students. Quantitative analysis of success factors contained in the existing data of the university, qualitative focus group discussions on students’ perceptions and a questionnaire with a qualitative and quantitative section on success factors were used. In recruiting students for Dietetics, strict adherence to admission criteria is necessary and support should be given to students on an individual basis to ensure the highest quality of student intake and eventual output. This study showed that Dietetics students realised their own responsibility to ensure their academic success, but participants also provided important insights on what can be done by the staff, the department and university in order to improve the academic success. This information is useful to others in the higher education community and also in other programmes in health sciences. More research on the perception of staff regarding academic success factors is needed and various intervention strategies to improve success can then be investigated.